2009
DOI: 10.3109/17453670903316819
|View full text |Cite
|
Sign up to set email alerts
|

High failure rate of the Duraloc Constrained Inlay

Abstract: Background and purpose After total hip arthroplasty, dislocations are a frequent complication and are difficult to treat in some patients. A great variety of implants and antiluxation mechanisms are used in surgical therapy.Methods 8 patients had 9 Duraloc Constrained Inlays implanted at our clinic between October 2003 and November 2006, for recurrent dislocations. A retrospective follow-up study was carried out.Results All patients suffered a failure of the expanding ring, the metal ring being squeezed out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…Recent attention has focused on the difference of outcome between revision rate reported in the peerreviewed literature and those in national joint arthroplasty registers. Findings were similar to those of our study for implants used in either field: THA, total knee arthroplasty, or total ankle arthroplasty [5][6][7][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 91%
“…Recent attention has focused on the difference of outcome between revision rate reported in the peerreviewed literature and those in national joint arthroplasty registers. Findings were similar to those of our study for implants used in either field: THA, total knee arthroplasty, or total ankle arthroplasty [5][6][7][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 91%
“…The choice of the Duraloc constrained liner also appears to be a limitation. This was associated with a high failure rate, 39 which was confirmed in our series in which 6 (24%) of the first 25 revisions re-dislocated. This device, however, can be used successfully if the surgeon is aware of the double click at the time of reducing the constrained liner.…”
Section: Discussionsupporting
confidence: 72%
“…Berend et al 11 reported a long-term failure rate of 42.1% with the tripolar constrained implant, while Labek et al 12 reported a 100% failure rate using the Duraloc constrained inlay (Depuy/Johnson and Johnson, Warsaw, IN). Survival at 10.2 years was 90% with the tripolar constrained implant using component failure as the end-point, and 68% for all modes of failure.…”
Section: Constrained Linersmentioning
confidence: 99%